2002
DOI: 10.1074/jbc.m109870200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Regulation of Insulin-like Growth Factor-binding Protein-1 Gene Expression Is Dependent on the Mammalian Target of Rapamycin, but Independent of Ribosomal S6 Kinase Activity

Abstract: Insulin inhibits the expression of the hepatic insulinlike growth factor-binding protein-1 (IGFBP-1) and glucose-6-phosphatase (G6Pase) genes. The signaling pathway that mediates these events requires the activation of phosphatidylinositol 3-kinase, whereas transfection studies have suggested an involvement of Akt (protein kinase B) and FKHR, a transcription factor regulated by Akt. We now demonstrate that insulin repression of endogenous IGFBP-1 gene transcription was blocked by rapamycin or by amino acid sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 62 publications
6
61
0
Order By: Relevance
“…Thus, several such studies have concluded that insulin regulates the expression of these genes through distinct pathways. For example, insulin regulation of IGFBP-1 gene expression (81,82), although not PEPCK (83) or G6Pase (43) gene expression, is dependent on the mammalian target of rapamycin. Moreover, it is likely that the regulation of these genes is highly complex, given the large number of kinase inhibitors/activators that can affect their expression (84 -86).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several such studies have concluded that insulin regulates the expression of these genes through distinct pathways. For example, insulin regulation of IGFBP-1 gene expression (81,82), although not PEPCK (83) or G6Pase (43) gene expression, is dependent on the mammalian target of rapamycin. Moreover, it is likely that the regulation of these genes is highly complex, given the large number of kinase inhibitors/activators that can affect their expression (84 -86).…”
Section: Discussionmentioning
confidence: 99%
“…A dissociation between TOR kinase activity and rapamycin action has been already described (40,41). Additionally, a recent example of discrepancy between rapamycin inhibition and p70S6K activity could be found in (42). At any rate, an inhibitor of a S6K cellular pool should be enough to explain the profound physiological effect of rapamycin on chemotaxis.…”
Section: Human Neutrophils Express P70s6k and Gm-csf Increasesmentioning
confidence: 99%
“…Transient transfections. A reporter construct encompassing a luciferase cDNA under the control of a thymidine kinase gene promoter containing the IGFBP1 thymine-rich insulin response element (BP1-TIRE) was transfected with or without an expression construct for glutathione-S-transferase-FOXO1 (pEBG-FOXO1) into HL1c cells as previously described (26,33). Cells were incubated for 16 h with hormones as indicated in the figure legends before harvesting and assaying for luciferase activity.…”
Section: Methodsmentioning
confidence: 99%
“…6). Cells tranfected with BP1-TIRE (a FOXO reporter construct) express luciferase activity that is reduced ϳ50% by incubation with insulin (26). The expression of a glutathione S-transferase-FOXO1 fusion protein induces luciferase expression, but this remains sensitive to repression by insulin (Fig.…”
Section: Akti-1/2 Is a Specific Inhibitor Of Pkb␣ And Pkb␤mentioning
confidence: 99%
See 1 more Smart Citation